MODERN METHODS OF ANALYSIS OF OPERATION OF BANK: SOLVE THE PROBLEM ASPECTS - Коц, Григорій Павлович; Кузьомін, Олександр Якович; Ляшенко, В. В. (Eastern-European Journal of Enterprise Technologies, 2010)
A classical interpretation model of the effective bank management in the relationship terms of its liquidity and profitability are considered. The space-time dynamics issue for the analysis of banking activities was summarizes. The microsituation essence for the comparative analysis was shown.